(untitled) (Al-Insyirah Midwifery: Jurnal Ilmu Kebidanan (Journal of Midwifery Sciences), 2025)
Antenatal care classes have been targeted at pregnant women only, without the participation of husbands or families. The inhibiting factors include knowledge, attitude, occupation, support from husbands to accompany pregnant women during activities. There is still little research on male involvement in ANC classes, where the pregnancy period is a phase of changing the husband’s role as a prospective father to become a parent. The type of research is a systematic review with the method used is PRISMA (Preferred Reporting Items for Systematic Reviews). Data were accessed from various database sources such as; Google Scholar, PubMed, Science Direct, Sage Pub, Cochrane. The literature was reviewed from 2020 to 2024 which was original experimental research with designs; randomized controlled trial, quasy experiment, and pre experiment. There were 9 suitable research articles. The subjects were pregnant women and their husbands/partners. The results were that participation in pregnant women’s classes attended by husbands can improve the quality of the father’s antenatal partnership and the father’s bonding attachment with his future baby, minimal complication delivery outcomes are 2.5 times better than those who do not attend classes. Class activities for pregnant women accompanied by their husbands are given material that suits the needs of pregnancy can increase the knowledge of mothers and husbands and increase the frequency of pregnancy control to health workers. The conclusion is that pregnancy classes attended by husbands are a good place to increase the participation, maintain pregnancy and the birth of healthy and quality babies.